Ta có : 2 + 4 + 6 + ... + 2(n - 1) + 2n = 210
<=> 2[1 + 2 + 3 + ... + (n - 1) + n] = 210
<=> 1 + 2 + 3 + ... + n = 105
<=> [(n - 1) : 1 + 1)(n + 1) : 2 = 105
<=> n(n + 1) = 210
<=> n(n + 1) = 14.15
=> n = 14
Vậy n = 14
b) Ta có : 1 + 3 + 5 + ... + (2n - 1) = 225
<=> [(2n - 1 - 1) : 2 + 1](2n - 1 + 1) : 2 = 225
<=> n2 = 225
<=> n2 = 152
<=> n = 15
Vậy n = 15
TL:
Ta có : 2 + 4 + 6 + ... + 2(n - 1) + 2n = 210
<=> 2[1 + 2 + 3 + ... + (n - 1) + n] = 210
<=> 1 + 2 + 3 + ... + n = 105
<=> [(n - 1) : 1 + 1)(n + 1) : 2 = 105
<=> n(n + 1) = 210
<=> n(n + 1) = 14.15
=> n = 14
Vậy n = 14
b) Ta có : 1 + 3 + 5 + ... + (2n - 1) = 225
<=> [(2n - 1 - 1) : 2 + 1](2n - 1 + 1) : 2 = 225
<=> n2 = 225
<=> n2 = 152
<=> n = 15
Vậy n = 15
HT
TL:
a) n =14
b) n=15
-HT-
TL:
a) n= 14
b) n =15
-HT-
TL:
n = 14
n = 15
HT